INTERCONNECTION AND INTERDEPENDENCE OF KEY ECONOMIC SECTORS - AGRICULTURE AND TOURISM IN THE CONDITIONS OF A PANDEMIC CRISIS - Marina NIKOLOVA; Pavlin PAVLOV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The rural development policy in Bulgaria is aimed at achieving sustainable development of the economic sectors, as the rural area is a place for development not only for agricultural activities, but also it offers good prospects for economic development on a regional scale, through adequate business support, job creation and tourism development. Therefore, the interconnection and interdependence between the two economic sectors is especially important to find opportunities for the development of alternative tourism with the formation of unique tourism products and the application of environmentally-friendly agricultural practices in order to achieve higher living standards and economic benefits for local communities. The problem is that the current pandemic conditions of last year and this year impose a number of restrictions to a greater or lesser extent on each of the economic sectors. The aim of our research is related to the study of interconnection and interdependence of key economic sectors – agriculture and tourism in crisis conditions. The research methods used in the study include: basic scientific research methods, questionnaire survey, summary and synthesis, logical method, tabular and graphical presentation of characteristics and trends. The results of the research can be systematized in several directions: analysis of the connections and interdependence of the sectors through the opportunities for creation of unique tourist products and through diversification of the activities in the rural areas. In conclusion, the pandemic inevitably affects the economic sectors, with greater constraints on the tourism business, where the preferences of potential tourists are focused on domestic alternative tourism. In the construction of unique and specific tourist products in rural areas, the relationship agriculture – tourism is strongly emphasized in terms of requirements for clean and healthy foods, incl. organic food or the purchase of local food products from the region. The diversification of activities in rural areas through the development of tourism provides an opportunity for the development of entrepreneurial initiatives. The strong connection and interdependence between the economic subjects in the indicated economic branches of key importance is fully manifested in a good combination of the interests of all participants concerned in the process of development of the specific territory/region.